Efektivitas Model Gallery Walk Berbantuan Alat Peraga Terhadap Hasil Belajar Matematika - Tuto Laba, Maria Eveline; Prayitno, Sudi; Junaidi, Junaidi (FKIP Universitas Mataram, 2025)
This research is motivated by the low mathematics learning outcomes of students, which was caused by the use of conventional learning models. The purpose of this study was to examine the effectiveness of the gallery walk model assisted by teaching aids on mathematics learning outcomes of SMP Negeri 1 Gunungsari students in the 2024/2025 school year. This research employs a quasi experimental design method with a quantitative approach and a posttest-only control design. The sampling technique used is cluster random sampling technique. The samples in this research are students of class VIII D as the experimental class and class VIII A as the control class. The experimental class is given treatment with a gallery walk model assisted by props while the control class is given treatment using a conventional model. The data collection techniques used are tests and observations. The average posttest score of the experimental class (79,09) is higher than the control class (74,50). Based on the calculation of the independent t-test using SPSS with a significance level of 5%, the , so it’s concluded that the use of the gallery walk model assisted by teaching aids is effective on the mathematics learning outcomes of class VIII students of SMP Negeri 1 Gunungsari in the 2024/2025 academic year.